Aetiology of mitral regurgitation differentially affects 2‐year adverse outcomes after MitraClip therapy in high‐risk patients. (July 2013) - Rudolph, Volker; Lubos, Edith; Schlüter, Michael; Lubs, Daniel; Goldmann, Britta; Knap, Malgorzata; de, Tjark; Treede, Hendrik; Schirmer, Johannes; Conradi, Lenard; Wegscheider, Karl; Reichenspurner, Hermann; et al.
<x xml:space="preserve">Abstract</x> Aims To assess, and identify predictors of, 2‐year adverse outcomes of surgical high‐risk patients after successful MitraClip therapy (MC), differentiated by the aetiology of mitral regurgitation (MR). Methods and results Kaplan–Meier analysis was used to assess survival free from death, heart failure rehospitalization, and reintervention up to 2 years in 202 successfully treated patients [74 ± 9 years, 132 men (65%); secondary MR aetiology in 140 patients, primary MR in 62]. Predictors for study endpoints were determined using Cox regression analyses. Mortality was 20% at 1 year and 33% at 2 years in both primary and secondary MR patients; independent predictors of death were reduced forward stroke volume, impaired LV function, and renal failure in primary MR, yet only an increased logistic EuroSCORE in functional MR patients. The rate of rehospitalizations was not different between the patient subgroups for 6 months, but then diverged significantly in favour of primary MR patients (estimated 2‐year incidence, primary MR 40% vs. secondary MR 66%). No predictor was found for primary MR patients, but increased LV end‐diastolic volume significantly increased the risk of rehospitalization in functional MR patients. Reinterventions were overall rare (7.4% at 1 year, 9.7% at 2 years); primary MR patients required all except one reintervention within 2 months of MC, with again no predictors found, whereas secondary MR patients (all except one with discharge MR of 2+) exhibited a steadily declining freedom from reintervention curve throughout follow‐up. Conclusion MR aetiology affects rehospitalization and reintervention, but not mortality, differently after successful MC.